Critical role of G3BP1 in bovine parainfluenza virus type 3 (BPIV3)-inhibition of stress granules formation and viral replication - Liu, Nian; Yang, Wei; Luo, Lingzhi; Ma, Mingshuang; Cui, Jin; Dong, Xiumei; Li, Yijing (Frontiers in Immunology, 2024)
Bovine parainfluenza virus (BPIV), a significant causative agent of respiratory syndromes, primarily affects the local or systemic immunity of a host. Stress granules, which serve as a crucial platform for innate immunity, play a pivotal role in the response to viral infections. Among these proteins, G3BP1, a nucleating protein, promotes the assembly of stress granules and is involved in antiviral functions. However, it remains unclear whether BPIV3 infection leads to stress granules formation and whether G3BP1 plays a role in this process and in viral replication. In the present study, BPIV3 infection was found to elicit phosphorylation of the eIf2α protein. However, it did not induce the assembly of stress granules; rather, it inhibited the formation of stress granules and downregulated the expression of G3BP1. G3BP1 overexpression facilitated the formation of stress granules within cells and hindered viral replication, while G3BP1 knockdown enhanced BPIV3 expression. These findings suggest that G3BP1 plays a crucial role in suppressing stress granule formation and BPIV3 viral replication, and provide significant insights into the mechanisms by which BPIV3 evades the host's antiviral immunity to support its own survival. calves. BPIV3 infection is now a major cause of morbidity and economic losses in cattle worldwide (1-3). The mechanisms underlying the pathogenicity of and immunosuppression by BPIV3 remain unclear, and there is currently no targeted treatment available for BPIV3 infection. A better understanding of the mechanisms underlying BPIV3 pathogenesis and the interactions between BPIV3 and its host will facilitate the development of more effective control strategies.Various external stress stimuli, such as heat shock, oxidative stress, nutritional deficiencies, and the viral infections can lead to the formation of stress granules (SGs) (4).